Dietary α-Linolenic Acid-Rich Flaxseed Oil Ameliorates High-Fat Diet-Induced Atherosclerosis via Gut Microbiota-Inflammation-Artery Axis in ApoE−/− Mice - Li, Yiwei; Yu, Zhi; Liu, Yuanyuan; Wang, Ting; Liu, Yajuan; Bai, Zhixia; Ren, Yi; Ma, Huiyan; Bao, Ting; Lu, Haixia; Wang, Rui; Yang, Libo; et al. (Frontiers in Cardiovascular Medicine, 2022)
Atherosclerosis (AS) is closely associated with abnormal chronic low-grade inflammation and gut dysbiosis. Flaxseed oil (FO) rich in omega-3 polyunsaturated fatty acids (PUFAs), mainly alpha-linolenic acid (ALA, 18:3 omega-3), has been demonstrated to exhibit pleiotropic benefits in chronic metabolic diseases. However, the impact of dietary ALA-rich FO on AS and associated underlying mechanisms remains poorly understood. Thus, the present study was designed as two phases to investigate the effects in atherosclerotic Apolipoprotein E (ApoE)-/- mice. In the initial portion, ApoE-/- mice were randomly allocated to 3 groups: control group (CON), model group (MOD) and FO-fed model group (MOD/FO) and treated for 12 weeks. The second phase used antibiotic (AB)-treated ApoE-/- mice, which were divided into 2 groups: AB-treated model group (AB/MOD) and FO-fed AB-treated model group (AB/FO). In the results, dietary ALA-rich FO administration ameliorated atherosclerotic lesion, as well as the parameters of AS (body weights (BWs) and total bile acids (TBA)). Chronic systemic/vascular inflammatory cytokines and in situ macrophages (Mψs) were reduced with FO intervention. In addition, FO improved gut integrity and permeability by decreasing plasma lipopolysaccharide (LPS). Moreover, gut dysbiosis and metabolites (short-chain fatty acids (SCFAs) and bile acids (BAs)) in AS were modulated after FO treatment. Intriguingly, during AB-treated condition, significantly weakened amelioration of FO-treated on AS proposed that intestinal microbiota contributed to the FO effects. Correlation analysis showed close relationships among gut bacteria, metabolites and inflammation. Collectively, these results suggested that dietary ALA-rich FO ameliorated AS in ApoE-/- mice via the gut microbiota-inflammation-artery axis.